ANALISIS FAKTOR YANG MEMPENGARUHI PENYERAPAN TENAGA KERJA DI PROVINSI JAMBI - Muhammad Syafri; Zulfanetti Zulfanetti (Universitas Batanghari Jambi, 2018)
Jambi Province is one of the areas in Indonesia with a relatively high population growth is inseparable from the problem of employment. Problems encountered include increased workforce higher than labor absorption. Efforts to increase labor absorption can not be separated from influencing factors such as GRDP, provincial minimum wage, government expenditure. This study aims to analyze the effect of GRDP, Province Minimum Wage, Government Expenditure on Employment Absorption in Jambi Province during the period of 1997-2015. This research is expected to be used as one of the benchmarks for government and private sector to better pay attention to the level of employment in Jambi Province. The type of research used is descriptive quantitative with used secondary data and analysis by time series data, from 1997 to 2015 and used the Ordinary Least Square (OLS) regression analysis with the help of EVIEWS 9.0 software. The result of this research shows that partially PDRB variable in PDRB has significant effect to the absorption of manpower in Jambi Province. While the variables of UMP and Government expenditure did not affect the absorption of manpower in Jambi Province period 1997 - 2015. The coefficient of determination (R2) showed that the independent variables studied were able to explain 91 percent of labor absorption and the remaining 9 percent was explained by other variables not studied.Keywords: Employment Absorption, GRDP, UMP and Government expenditure